INTEGRASI NILAI-NILAI ISLAM DENGAN MATERI HIMPUNAN (KAJIAN TERHADAP AYAT-AYAT AL-QURâAN) - Nihayati, Nihayati (JURNAL e-DuMath, 2017)
Education in Indonesia is expected to form a human who has a strong Akidah, better Syariah and good Morals. As the result of imbalance between Akidah, Shariah and morals,Â many of students violating the rules, norms and ethics both in society and religion. This study aimed to examine the verses of Al-Quran relating to the mathematical set and illustrated with Venn diagrams. The way to analyze is to describe the verses of the Quran relating to the set of values of Akidah, Shariah and morals. The results of this research were in the form description of the value of akidah with verses of Al-Qurâan Al-Anam verse 128, Al-Waqiah verses 7-14, the Al-Fatihah verse 7, Taha verse 6. Value syari ah contained in the Quran Al-Anam verse 128, Al-Waqiah verses 7-14, the Al-Fatihah verse 7. Value morals contained in the Quran Al-Anam verse 128, Al-Waqiah verses 7-14, the Al-Fatihah verse 7.